ANALISIS PENGARUH BIAYA KUALITAS TERHADAP TINGKAT KEUNTUNGAN PERUSAHAAN (STUDI KASUS PADA CV. MERANTI MANUNGGAL FURNITURE) - Winarno, Slamet Heri (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2015)
This research aimed to analyze the effect of cost of quality to the profitability. This research is quantitative, the data used is quality costs consist of t Prevention cost, appraisal cost, internal failure cost, external failure cost  and profitability. The data was taken from the financial statements CV Meranti Manunggal Furniture 2008-2014. The method used in this research is the statistic method  with Multiple Regression Analysis and SPSS. The results showed that there is a positive and significant effect on the cost of quality to the profitability is reflected in the mathematical equation EBIT=5,425+0.409X1+0.277X2+0.246X3-0.511X4. Simultaneously and partially all independent variables showed a significant effect on the dependent variable, is reflected from the F test and t test. Based on analysis of the data in this study can be concluded that the cost of quality positive and significant impact on the level of profits CV.Meranti  Manunggal FurnitureKeywords: Prevention Cost, Appraisal Cost,  Failure Cost, Profit (EBIT)